2008
DOI: 10.2214/ajr.07.2195
|View full text |Cite
|
Sign up to set email alerts
|

Midterm Results of Percutaneous CT-Guided Aspiration of Symptomatic Lumbar Discal Cysts

Abstract: Percutaneous CT-guided aspiration is an effective method for the management of lumbar intervertebral discal cysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 11 publications
1
33
0
2
Order By: Relevance
“…These reports also showed favorable results, with no cases of recurrence. CTguided aspiration of the cyst contents was described in two reports with nine patients (16%) [11,16]. This method showed good results in eight patients and recurrence of the cyst in one patient (11%).…”
Section: Surgical Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…These reports also showed favorable results, with no cases of recurrence. CTguided aspiration of the cyst contents was described in two reports with nine patients (16%) [11,16]. This method showed good results in eight patients and recurrence of the cyst in one patient (11%).…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…In all cases of discal cysts reviewed in the literature, three cases (5.3%) showed spontaneous regression of the cyst after conservative treatment [3,5,6], five cases (9%) showed failure after conservative treatment and referred to surgery [4,9,12,20] and two cases showed recurrence of the cyst (3.5%) after CT-guided aspiration [11] and microsurgical resection [18]. The natural history of discal cysts is still unknown, however; these findings support the importance of the surgical treatment of discal cysts.…”
Section: Outcomementioning
confidence: 99%
“…Most discal cysts reported have been treated by open surgical excision (Chiba, Toyama et al 2001; or with some direct intervention, such as computed tomography-guided aspiration and steroid injection (Kang, Liu et al 2008). Recently, it was reported that a discal cyst was treated with a minimally invasive technique using PELD (Min 2006).…”
Section: Discal Cystmentioning
confidence: 99%
“…If an invasive strategy is necessary, an aspiration of the cyst versus a surgical technique should be weighed and considered. CT-guided aspirations of cysts, as detailed by Kang et al,3 demonstrated an 89% success rate (one out of the eight patients recurred). However, the location of the cyst will determine the feasibility of this treatment modality.…”
mentioning
confidence: 95%